Agency and aspiration in career narratives of men becoming teaching assistants - Meredith, Caroline Ann (2022)
Concerns about gendered attainment-gaps and the scarcity of men teaching in England’s primary schools underlie a popular and political assumption that recruiting more men to the sector will help to counter perceived gender inequalities in teaching and learning. Nevertheless, of nearly 390,000 Teaching Assistants (TAs) recruited since 2003 fewer than 10% are men. To better understand the barriers and affordances to men becoming TAs this study investigates what motivates men to become TAs. It seeks to understand their experiences, and how becoming a TA might aid their career aspirations. The narrative study utilised life-grid interviews to capture the career narratives of nine men who have become TAs. Graphic timelines illustrated and interpreted the narratives by plotting past events, present experiences and future aspirations which motivate and drive the careers of men becoming TAs. An iterative approach to analysis enabled investigation of the forces that influence careers, and the nature of self-directed, agential career-crafting. The findings suggest that whilst the primary education work-sector is gender-concentrated, the TA role itself is not inevitably gendered. Frequently, participants were motivated by a sense of vocation and wanting to make a positive contribution, whilst seeking a sustainable, viable career. The study found a significant relationship between aspirational career-thinking and agential career-crafting. Together, these offer fertile ground for an ambitious career trajectory. This study argues that when combined with lifelong learning, TA work can encourage aspirational career-thinking and strengthen individuals’ agency to craft a self-directed career with increasingly ambitious goals. This is an important finding in the context of attracting men into primary education and nurturing their ambitions, to encourage them to remain in the sector.